2010
DOI: 10.2134/jeq2009.0374
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients in Runoff from a Furrow‐Irrigated Field after Incorporating Inorganic Fertilizer or Manure

Abstract: Use of dairy manure to supply crop nutrients is gaining broader acceptance as the cost of fertilizer rises. However, there are concerns regarding manure's effect on water quality. In 2003 and 2004, we measured sediment, NO3–N, NH4–N, K, dissolved reactive P (DRP), and total P (TP) concentrations in runoff from furrow irrigated field plots (6–7 irrigations yr−1) cropped to corn (Zea mays L.) in the semiarid climate of southern Idaho. Annual treatments included 13 (Year 1) and 34 Mg ha−1 (Year 2) stockpiled dair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…1, six runoff water quality samples per irrigation were collected at 5 min and 0.5, 2, 8, 14, and 24 h aft er furrow advance. Th ese data verifi ed the results from other studies (Lentz and Lehrsch, 2010) showing that the greatest changes in constituent concentrations occurred in the fi rst 4 to 5 h aft er runoff began, with only minor changes occurring thereaft er. Furthermore, the 0.5-h sample time was not as defi nitive as a 1-h sampling time because runoff rates early in the runoff period were relatively small.…”
Section: Sampling and Analysessupporting
confidence: 84%
See 4 more Smart Citations
“…1, six runoff water quality samples per irrigation were collected at 5 min and 0.5, 2, 8, 14, and 24 h aft er furrow advance. Th ese data verifi ed the results from other studies (Lentz and Lehrsch, 2010) showing that the greatest changes in constituent concentrations occurred in the fi rst 4 to 5 h aft er runoff began, with only minor changes occurring thereaft er. Furthermore, the 0.5-h sample time was not as defi nitive as a 1-h sampling time because runoff rates early in the runoff period were relatively small.…”
Section: Sampling and Analysessupporting
confidence: 84%
“…Dissolved reactive P concentrations in runoff are less correlated with sediment, and irrigation mean values range from 0.04 to 0.18 mg L −1 (Fitzsimmons et al, 1972;Westermann et al, 2001;Bjorneberg et al, 2006;Lentz and Lehrsch, 2010). Runoff DRP was found to be infl uenced by furrow length, the residence time of water in the furrow (stream velocity), the quantity of crop residue exposed in the furrow (Bjorneberg and Aase, 2004;Westermann et al, 2001), and infi ltration fraction (Lentz and Lehrsch, 2010). Fitzsimmons et al (1972) reported mean N concentrations in a random sampling of surface irrigation infl ow and runoff waters from 30 farms in southwest Idaho.…”
Section: R D Lentz* D T Westermann (Retired)mentioning
confidence: 99%
See 3 more Smart Citations